(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the autumn season is represented as an artistic image in Rauf Parfi’s work. Through this image, the artist describes life and life. The sentences "blue season" and "blue leaves" reveal the main content of our article.